Enhancing Student Learning Outcomes Through Creative Power Point Media on Addictive Substances Material - Fariel Ishaak; Hafiz Muhmmad Asim; Ashwin Polishetty; Alisa Stanton; Stephen Gomez; André Moulakdi (Classroom Experiences, 2025)
The cause of poor student learning outcomes is known through the teacher's inaccuracy in choosing learning methods and media. This media is what determines student activities in learning to achieve the expected goals. This study aims to improve student learning outcomes in addictive substance material for second class at Algemene Middelbare School (AMS) using power point media. The subjects of this study were 33 students of Second Class AMS. Learning improvement actions were carried out in 2 cycles. The expected benefits of this study are: For teachers, it is expected to broaden their horizons and improve teacher professionalism, for students of course to improve their learning achievements, and for institutions or schools it is expected to be useful as an innovation in teaching and learning. The results of this study are that the use of power point media for addictive substance material in second class at AMS has proven to be very influential on learning outcomes. This can be seen from the percentage of learning outcomes in cycle 1 to cycle 2 increasing. From the results of the evaluation, students who obtained scores above the minimum completion criteria in cycle 1 were 8 students with a percentage of 24.2% and in cycle 2 there were 28 students with a percentage of 84.8%.